2008
DOI: 10.1590/s0080-62342008000100021
|View full text |Cite
|
Sign up to set email alerts
|

Eficácia da estufa de Pasteur como equipamento esterilizante em consultórios odontológicos

Abstract: Este estudo objetivou avaliar a eficácia do uso da estufa de Pasteur, como equipamento esterilizante, em consultórios odontológicos, por meio de monitoramento biológico. Para esta avaliação foram consideradas: adequação no carregamento dos materiais no equipamento, tempo/temperatura utilizados e manutenção preventiva da estufa. Os dados foram coletados em 101 consultórios odontológicos, no Distrito Central de Goiânia-GO, Brasil, por meio de observação, entrevista e realização de teste com indicador biológico. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 2 publications
(2 reference statements)
1
2
0
2
Order By: Relevance
“…Temperatures taken from two different thermometers diverge because the thermometer in the device shows a temperature higher than that reached within the load; the reason is that the device's thermometer is closer to the equipment's electrical circuits (1,7) . These findings also coincide with those of other studies (15)(16)(17)(18) . A study carried out in Canoas, RS, Brazil in 27 dental offices revealed that an adjunct thermometer was used in 24 (88.9%) offices, which shows better sterilization control when compared to data from this investigation (19) .…”
Section: Six Classes Of Chemical Indicators Are Currently Availablesupporting
confidence: 93%
See 2 more Smart Citations
“…Temperatures taken from two different thermometers diverge because the thermometer in the device shows a temperature higher than that reached within the load; the reason is that the device's thermometer is closer to the equipment's electrical circuits (1,7) . These findings also coincide with those of other studies (15)(16)(17)(18) . A study carried out in Canoas, RS, Brazil in 27 dental offices revealed that an adjunct thermometer was used in 24 (88.9%) offices, which shows better sterilization control when compared to data from this investigation (19) .…”
Section: Six Classes Of Chemical Indicators Are Currently Availablesupporting
confidence: 93%
“…This relation is essential for ensuring efficacy of the cycle, noting that timing of exposure should begin only when a given temperature is reached; time spent to heat the equipment should not be taken into account (1,7) . A study conducted in 101 dental offices in the central region of Goiania concluded that intervenient factors with greater significance related to sterilization failures were: not complying with the time/ temperature ratio recommended for the sterilization cycle and the absence of an adjunct thermometer to control the temperature of the cycles, aspects ratified in microbiological tests that were positive in 46 (45.5%) of the evaluated cycles (16) . Similar data were found in other studies that evaluated sterilization in Pasteur's ovens in dental offices (17)(18) .…”
Section: Six Classes Of Chemical Indicators Are Currently Availablementioning
confidence: 99%
See 1 more Smart Citation
“…Sendo assim, de um modo geral, esse processo pode ser realizado através de métodos físicos, químicos e físico-químicos 23 .…”
Section: Introductionunclassified
“…É comum o uso do álcool etílico a 70% nos procedimentos de descontaminação desse instrumento. Um estudo (13) verificou (19) , como na atenção básica (20) .…”
Section: Introductionunclassified